Traffic Calming Measures: An Evaluation of the Effect on Driving Speed - Vaitkus, Audrius; Čygas, Donatas; Jasiūnienė, Vilma; Jateikienė, Laura; Andriejauskas, Tadas; Skrodenis, Dovydas; Ratkevičiūtė, Kornelija (Promet - Traffic&Transportation, 2017)
Road accidents are one of the leading causes of death in the world, particularly among young people. Excessive speed is one of the main risk factors in road traffic safety, increasing accident probability and affecting accident severity. Experimental research of the traffic calming measures allocation effect on the driving speed is presented in this paper. The research has been carried out on two aspects. The first one with respect to the mean speed and the second one regarding instantaneous speed. However, the paper is not only restricted by the above research. Standardized survey interview and questioning, a survey of public opinion, was carried out to find out the road users’ opinions about the need for traffic calming measures and speed control measures. Finally, the authors presented their insights and recommendations for the installation of speed humps and gateways and their optimum spacing.